977 Breaking Out of Tradition: Designing Escape Rooms as Novel Simulation. (19th August 2022) - Badenoch, T; Benton, K; Jacobs, E; Law, S; Ahmed, M; Curtis, A; Everett, S; Hunter, I; Bamford, R
Abstract: Aim: The emerging field of gamification, the addition of game play elements to non-game settings, is widely used in business and is increasingly being used in education. Successful methods have included live leader boards and a web-based game solving a protein folding conundrum. Method: We designed an escape room (ER), incorporating gaming elements, focussing on communication in a surgical environment. A cross over study was delivered to 4 th year medical students, comparing traditional simulation. The ER included logic puzzles, hidden clues, padlocked boxes, and surgical skills appropriate to their level. Self-reported engagement and teamwork were recorded, as was observed teamwork and communication skills. Results: Self-reported engagement was very high for the students compared to more traditional simulation, including better understanding of effective communication strategies. The ER group were less likely to self-identify learning points but structured debrief mitigated this difference. Conclusions: Gamification techniques can be integrated with good engagement and educational outcomes and should be considered as an adjunct to existing simulation strategy.